RESEARCH COTTON MECHANISATION IN ASIAN COUNTRIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Cotton Harvesters has proven to be a promising approach for cotton harvesting in India and developing countries. However, challenges still remain in its implementation in India though considerable progress has been made in recent years. Developed countries have 100% mechanized cotton picking. With increasing labor charges and its unavailability, mechanization has gained pace in Indian agriculture sector. This review paper provides an overview of cotton harvesters and its various types. It also covers the anatomy of cotton plant, production, and its importance in Indian economy. Indian cropping pattern are studied in detail and various mechanism discussed and their pros and cons are evaluated in this paper.